PENYULUHAN KONDISI UDARA DI AREA KERJA KAMPUNG OPAK KECAMATAN MAJASARI PANDEGLANG - Arta Rusidarma Putra; Suhandi Suhandi; Ombi Romli (Jurnal Abdimas Bina Bangsa, 2024)
Opak is a type of crunchy and dry food like crackers which is very popular among people because of its taste and economic value for the community. The increasing amount of production will have a major impact on air conditions in the work environment because production activities produce smoke that comes from traditional processing processes using wood and coconut fiber as heat sources. The climate of the work environment greatly influences human body temperature and results in workload. Physical activity in a hot work environment also has an effect on reducing the achievement of the activities carried out and increasing the risk of disease, dehydration and hyperthermia. This activity aims to convey knowledge to business actors and workers regarding air conditions in the work environment as well as safe working time limits at work. The method used is a survey and outreach method. This activity results in increased knowledge of business actors and workers regarding air conditions in the work environment and creates a good work environment